El servicio al cliente como filosofía y factor de posicionamiento de las cooperativas de taxis - Vera Campuzano, Nury (2018)
The objective of this scientific paper is to socialize the customer service’s impact to taxi cooperatives in the province of Santa Elena as philosophy and positioning factor. All companies should seek customer satisfaction, especially in a competitive market where it is not only sufficient to meet the needs of these, but finding the best way to solve it. Those companies must implement appropriate actions oriented to the market and the target market preference. Taxi cooperatives should consider the excellence in customer service as part of the corporate philosophy, that is, having as a fundamental value of those who integrate a company, the service quality vocation, first of all, trying in this way, a harmonious environment between internal customers, and then, create a suitable interaction between internal and external customers regarding to the provision of service, so that external customers can be satisfied properly which the internal customers must feel identified with the corporate culture. In the province of Santa Elena, taxis sector does not project a strong image before their customers due to inadequate culture of customer service, lack of knowledge about the impact of marketing strategies in the mind’s users.